Southwest Pacific Ocean response to a warmer world: Insights from Marine Isotope Stage 5e. (23rd September 2013) - Cortese, G.; Dunbar, G. B.; Carter, L.; Scott, G.; Bostock, H.; Bowen, M.; Crundwell, M.; Hayward, B. W.; Howard, W.; Martínez, J. I.; Moy, A.; Neil, H.; et al.
<x xml:space="preserve">Abstract</x> [1] Paleoceanographic archives derived from 17 marine sediment cores reconstruct the response of the Southwest Pacific Ocean to the peak interglacial, Marine Isotope Stage (MIS) 5e (ca. 125 ka). Paleo‐Sea Surface Temperature (SST) estimates were obtained from the Random Forest model—an ensemble decision tree tool—applied to core‐top planktonic foraminiferal faunas calibrated to modern SSTs. The reconstructed geographic pattern of the SST anomaly (maximum SST between 120 and 132 ka minus mean modern SST) seems to indicate how MIS 5e conditions were generally warmer in the Southwest Pacific, especially in the western Tasman Sea where a strengthened East Australian Current (EAC) likely extended subtropical influence to ca. 45°S off Tasmania. In contrast, the eastern Tasman Sea may have had a modest cooling except around 45°S. The observed pattern resembles that developing under the present warming trend in the region. An increase in wind stress curl over the modern South Pacific is hypothesized to have spun‐up the South Pacific Subtropical Gyre, with concurrent increase in subtropical flow in the western boundary currents that include the EAC. However, warmer temperatures along the Subtropical Front and Campbell Plateau to the south suggest that the relative influence of the boundary inflows to eastern New Zealand may have differed in MIS 5e, and these currents may have followed different paths compared to today.